2016
DOI: 10.1523/jneurosci.1202-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Hypothalamic Area Glutamatergic Neurons and Their Projections to the Lateral Habenula Regulate Feeding and Reward

Abstract: The overconsumption of calorically dense, highly palatable foods is thought to be a major contributor to the worldwide obesity epidemic; however, the precise neural circuits that directly regulate hedonic feeding remain elusive. Here, we show that lateral hypothalamic area (LHA) glutamatergic neurons, and their projections to the lateral habenula (LHb), negatively regulate the consumption of palatable food. Genetic ablation of LHA glutamatergic neurons increased daily caloric intake and produced weight gain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
224
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(247 citation statements)
references
References 38 publications
15
224
1
Order By: Relevance
“…Stamatakis et al (2016) have confirmed those findings in transgenic mouse preparations in which LH neurons were transfected with photosensitive excitatory or inhibitory ion channels controlled by the VGluT2 promoter. Optogenetic stimulation of the VGluT2 controlled pathway produced mostly glutamate-mediated excitatory postsynaptic potentials.…”
Section: Afferent Connectionssupporting
confidence: 81%
“…Stamatakis et al (2016) have confirmed those findings in transgenic mouse preparations in which LH neurons were transfected with photosensitive excitatory or inhibitory ion channels controlled by the VGluT2 promoter. Optogenetic stimulation of the VGluT2 controlled pathway produced mostly glutamate-mediated excitatory postsynaptic potentials.…”
Section: Afferent Connectionssupporting
confidence: 81%
“…Intriguingly, optogenetic stimulation of glutamatergic projections from the neighboring endopeducular nucleus (EP) is also aversive 140 , suggesting that glutamatergic neuronal populations in the LHA, the zona inserta, and EP may share a common behavioral/circuit function. In our studies, we have also observed substantially weaker LHb innervation from LHA GABAergic neurons 113 . However, LHA VGat neurons appear to innervate midline thalamic structures just ventral to the LHb such as the periventricular thalamus (PVT), a brain region shown to produce GABA-mediated feeding 141 .…”
Section: Output Circuitry Of the Lhasupporting
confidence: 68%
“…4). Consistent with this, optogenetic inhibition of the LHA Vglut2 -LHb pathway enhances licking for a caloric reward and produces aversion when optogenetically activated 113 . Intriguingly, optogenetic stimulation of glutamatergic projections from the neighboring endopeducular nucleus (EP) is also aversive 140 , suggesting that glutamatergic neuronal populations in the LHA, the zona inserta, and EP may share a common behavioral/circuit function.…”
Section: Output Circuitry Of the Lhamentioning
confidence: 56%
See 2 more Smart Citations